Thermally enhanced TLD output: Impacts on the response curve. (July 2017) - Soliman, H.A.; Hassan, Mohamed A.; Esmat, Enas; Sadek, A.M.; Maghraby, Ahmed M.
Abstract: Pre-irradiation background reading of thermoluminescent LiF dosimeters results in severe changes in the glow curve qualitatively and quantitatively. Current work focuses on the possible changes in the response of TLD-700 dosimeters after this effect. This work examines changes in the level of the glow curve as a whole and on the level of individual peaks as well. It was found that the response of TLD-700 dosimeters has increased by factors ranging from 20% to 44% in terms of area under the glow curve. Changes in individual peaks were examined by performing deconvolution for the glow curves. Results confirmed that the response due to such effect is not uniform over the studied temperature range and each individual peak has its own behavior either in terms of peak area or peak intensity. It was observed that the third peak (P3 ) leads these changes as the change in its area after being exposed to this thermally enhanced thermoluminescence output (TETO) effect was in the range from 4.1 to 3.0 folds compared to the corresponding values obtained without reading the background prior to irradiation. Peak intensity possesses similar behavior where peaks P2 and P4 are following to P3 in their response, the rest of peaks are either neutral or have negative response to TETO. Response curves of each deconvoluted peak in terms of peak area and maximum intensity are analyzed over the range (0.05−30) Gy and discussed in details. Highlights: Reading background of LiF (TL) dosimeters before irradiation enhances their output. Glow curves area increases and changes in their shape. Deconvolution of the glow curves revealed the selective response to the suggested treatment. The third peak leads the response of the dosimeters to the suggested treatment.